Best Practices and Avoidances in Data Driven Social Media Marketing Campaign for Takaful Advisors (Open International Journal of Informatics, 2021)
Social media marketing aims to grow consumer brands in the landscape of consumer and firm interaction through the social media reach and engagement. In order to reach out to the right number of potential customers at the right time, Social Media Analytics (SMA) is a method to collect data from social media sites and analyse this data for the purpose of business decision making. This research explore the usage of social media analytics in running a brand awareness campaign for a takaful advisor. Data from Facebook Insights were used as a source of information to strategize post timing and content based on users’ responses and trends in order to reach and to engage with the right target audience. The result of the campaign shows that in general there are slight increases in the number of page likes, reach and engagement in the business page . Although the campaign did not achieved the key performance index set by the client, the study recommends best practices and avoidances in promoting takaful products on social media.
Keywords: digital marketing; brand awareness; entrepreneurship; takaful industry